Dance Culture in Search of the Ways of Personality Spirituality (Global Journal of Human-Social Science, 2024)
The purpose of the article is to substantiate the expediency of searching for ways of personal spirituality The work methodology is based on the use of methods of analysis synthesis and specification An analysis of the search for the ways of the individual s spirituality was carried out outlining which ones there are prospects for solving cross-cutting issues of cultural aesthetic intellectual and physical content Synthesis as a scientific method made it possible to systematize the patterns of relationships between dance culture and the essential basis of the spirituality of the individual The concretization method directed research in the direction of reconstruction of the multifacetedness of dance culture in the personality-process-culture system We parallelize the understanding of dance first of all with plastic expressiveness and scientific pulsation because dance demonstrates meaning and meaning mostly in movements rather than in words with a content full of culturally significant information The specified thesis can be substantiated by various aspects namely by the spirituality of the individual against the background of which the trajectory of semiotics linguistics symbolism phenomenology and textology should be considered The text of the article can be used in the preparation of lecture material on professional disciplines history of art culture methodology choreography music education The work claims to use a creative approach in practical teaching activities which will qualitatively affect the final result on the path of the individual s spirituality
Keywords: spirituality; personality; culture; dance; youth